Pengaruh Manajemen Laba Terhadap Nilai Perusahaan pada Industri Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017 - Hana Tamara Putri (J-MAS (Jurnal Manajemen dan Sains), 2019)
The purpose of this research is to analyze the effect of earnings management measured by real-based earnings management on  company value that mesured by price to book value ratio. This research was conducted in some manufacturing companies listed on the Indonesia Stock exchange for period of 2015-2017. The sample was selected as many as 34 companies. The method of analysis uses associate descriptive analysis with simply linier regression analysis tools by testing classical assumption, testing hypotheses and coefficient of determination. Based on the results of the study found that earnings management as measured by real based earnings management affect the company’s value.